RELATIONS WORK MOTIVATION AND STRESS LEVEL JOB PERFORMANCE EMPLOYEES AT KENTUCKY FRIED CHICKEN UGM - Murdo, Yuri (Management, 2010)
This study analyzes the relationship intend work motivation and the level of stress with employees performance in the Kentucky Fried Chicken UGM. Data used in this study is data from the Kentucky Fried Chicken Primary UGM. The analytical method used is a regression model, which used multiple regression. The results showed that, first there is a positive relationship between motivation working with work performance of 2.929, and there is a negative relationship between levels of stress with work performance of -572. Based on the R squere 0.523 = 52.3% stated the relationship between work motivation levels of stress with work performance is still in the medium category. The second figure 0.28 coefficient of work motivation, arttinya if moivasi as level of employment rose 1%, then presasi employment rose 0.28%, while the number of stress-level coefficient of -0.054 means that when stress levels increase by 1% then the performance increase 0.054%. Keyword : Work motivation, Stress, Performance